An Analysis of Students’ Errors In Transforming Active Into Passive Sentences at Bung Hatta University English Department - Adzanil Prima Septy; Riska Juliani (Journal on Education, 2023)
This research aims to investigate students’ errors in transforming active into passive sentences of simple past tense. This research is descriptive. The population of this research was the second-year students at Bung Hatta University English Department. A total sampling technique was applied in this research where there were 30 students involved in this study. The instrument for collecting the data was a writing test. To make the test reliable the researcher used the inter-rater technique. It was found that the reliability index of the test was 0.99 (very high correlation), which means that the test is reliable. The writing test is valid in terms of content because it covered all materials that students had learned. The result of this test showed that students make 1134.5 errors. It can be classified from the highest to the lowest errors: such as misformation (47.55%), misordering (26.80%), omission (23.45%), and addition (2.20%). This study recommends some future research to find out what the best solutions are to manage the best teaching practices to minimize the students’ errors in writing